(3eTjNI CHj GdehGgHs - (3CHh GdehGgH , eMeO Hf YHO GdHGbj Hf YHO GdbGOQ GdMfHdj,J (B1126 (3g` s ((3GdOQhjT QeVGf Hf NdjaI Hf oeQGO s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hCaVd GdUdGI hCJe GdJSdje Ydi SjOfG eMeO hYdi Bdg hUMHg CLeYjf s
(3BNQgG (B:s
(3hGdMeO ddg hMOg hUdGJg hSdGeg Ydi SjOfG eMeO hBdg hUMHg CLeYjf Bejf s
(3PcQ ajgG JQGLe eTGjNI heG bQCg Ydjge heG CNPg Yfge hQhGjI HCi fhY ef GfhGY GdELGRIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B123s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B143 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI GdGScOQjI (B((3L(B2262) s
Keywords: (3GdJGQjNs